Suplementação de óleo da polpa de buriti (Mauritia flexuosa) para prevenção das alterações metabólicas induzidas por dieta hiperlipídica em camundongos - Aydos, Leonardo Recena (2021)
Metabolic syndrome is present in a large portion of the world population, and the number of people affected is growing. Due to the impact on health and the economy caused by this condition, metabolic syndrome is currently considered a public health problem to be faced. Although the onset of the disease is multifactorial, food is one of the primary factors. For this reason, researchers around the world have been engaged in the search for foods with functional properties that can help in the treatment of metabolic syndrome and the risk factors associated with it. In this sense, buriti pulp oil (BPO), a food traditionally consumed by residents in the Pantanal, Cerrado, and Brazilian Amazon, due to being rich in oleic acid, tocopherols, and carotenoids, emerges as a portion of food with functional potential. Thus, this study aimed to evaluate the effect of BPO supplementation on metabolic disorders caused by a highfat diet. To verify this, an experimental study was carried out with four groups of C57bl/6 mice. One lean group with AIN-93M diet and control oil supplementation, one obese group with high-fat diet and control oil supplementation, and two obese groups with a high-fat diet and BPO supplementation in the amounts of 50 and 100 mg/kg. At the end of the experiment, we found that BPO worsened the metabolic state caused by the high-fat diet, worsening the risk factors associated with MS, such as abdominal circumference and retroperitoneal fat, serum levels of total cholesterol, uric acid, alanine transaminase, glucose, and triglycerides, in addition to renal fat, in addition to changes in glycemic control and oxidative stress markers. C57bl/6 mice fed a high-fat diet and supplemented with BPO preventively, that is, before the onset of the metabolic changes characteristic of obesity and metabolic syndrome, showed a worsening in the metabolic risk factors associated with these conditions. Keywords: buriti oil, metabolic syndrome, obesity